Provisions for breaking fasting after it begins - Comparative doctrinal study - Alreqaibah, Amjad Sulaiman (Journal of Islamic Sciences, 2022)
The research aimed to study the provisions of interrupting the fast after initiating it and revealing the jurisprudential effects of interrupting the fast. And adopting the inductive approach in writing the research, and the researcher reached results, the most important of which are: -That whoever starts a fast and then intends to interrupt it, his fast is interrupted by this intention, and he must make up for that day. -That whoever begins a consecutive fast and then interrupts it for an accident, the sequence is not interrupted, and what preceded of his fast is valid and builds upon it. The vow then cut it off. Either the amputation was for an excuse or without an excuse. If it was for an excuse, he is given a choice between appealing without penance, and building on the above, but if the amputation was without an excuse, he must appeal.